In vitro assessment of antimicrobial activity of Pothomorphe umbellata extracts against Enterococcus faecalis - Emilio C Sponchiado; Juliana V Pereira; André AF Marques; Lucas da Fonseca Roberti Garcia; Suzelei C França (Wolters Kluwer Medknow Publications, 2014)
Background : Due to the complex anatomy of the root canal system, biomechanical preparation is not able to completely eliminate all microorganisms present in the endodontic infections, making it necessary the use of an intracanal medication. Aim: The aim of this study was to assess the antimicrobial activity of an intracanal medication containing the ethyl-acetate fraction of Pothomorphe umbellata against Enterococcus faecalis. Materials and Methods: Fifty seven human maxillary canine teeth were used, of which 54 were infected with E. faecalis every 72 h, for 28 days, and cultured for 24 h. Contaminated teeth were randomly separated into three groups (n = 18) and treated as follows: Group I - calcium hydroxide-based medication; Group II - P. umbellata-based medication; Group III - contaminated teeth without medication. Three teeth were used as negative control. After 7, 14 and 28 days of treatment, six teeth from each group were assessed for the level of microbial growth after each period of treatment. Results: The intracanal medication containing P. umbellata was effective against E. faecalis after 7, 14, and 28 days of treatment without statistically significant difference in comparison to calcium hydroxide treatment (Kruskal-Wallis test, P > 0.05). Conclusion: Ethyl-acetate fraction of P. umbellate was efficient against E. faecalis, making this phytotherapy a viable option for endodontic treatment.